2015
DOI: 10.1088/0264-9381/32/5/055013
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the geometrical stability in square ring laser gyroscopes

Abstract: Abstract. Ultra sensitive ring laser gyroscopes are regarded as potential detectors of the general relativistic frame-dragging effect due to the rotation of the Earth: the project name is GINGER (Gyroscopes IN GEneral Relativity), a ground-based triaxial array of ring lasers aiming at measuring the Earth rotation rate with an accuracy of 10 −14 rad/s. Such ambitious goal is now within reach as large area ring lasers are very close to the necessary sensitivity and stability. However, demanding constraints on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
(33 reference statements)
0
27
0
Order By: Relevance
“…We have demonstrated that, when the lengths of the two diagonals are locked to the same value, the perturbations to the mirror positions affect only quadratically the ring laser perimeter and scale factor 9 . In this case, the regular square geometry corresponds to a saddle-point of the perimeter, and so the scale factor fluctuations are minimized.…”
Section: The Gp2 Rl Gyroscopementioning
confidence: 96%
“…We have demonstrated that, when the lengths of the two diagonals are locked to the same value, the perturbations to the mirror positions affect only quadratically the ring laser perimeter and scale factor 9 . In this case, the regular square geometry corresponds to a saddle-point of the perimeter, and so the scale factor fluctuations are minimized.…”
Section: The Gp2 Rl Gyroscopementioning
confidence: 96%
“…S depends basically on the geometry, the quality of the mirrors, the pressure and composition of the gas mixture, and the plasma. Suitable control strategy for the geometry of the square ring laser has been studied and it is at present under study [30,31], two colocated devices will have equal gas mixture and pressure, each mirror can be characterised and they can be interchanged, accordingly the realisation of two RLs with equal scale factors is feasible. In order to estimate the requirements for the Lense-Thirring test at ρ = 1%, we have studied the specifications for η ∼ 10 −10 and η ⊥ ∼ 3.510 −10 (LT test).…”
Section: Error Budget and Specifications Of The Experimental Apparatusmentioning
confidence: 99%
“…While monolithic cavities made of ultra-low expansion materials, like the Gross ring G in Wettzell, have an excellent passive stability, they are not suited to form 3D arrays of very large size. On the other side, heterolithic systems require active stabilization, which is achieved by active control schemes of the cavity geometry, exploiting very accurate optical wavelength references 14,15 . The present structure of GINGERino does not allow the full implementation of these techniques, and this sets a limit to its present long term stability.…”
Section: Gingerino Working Principle and Experimental Setupmentioning
confidence: 99%